Factors leading to voter buying in the elections of the 18th Jordanian House of Representatives from the point of view of voters - Alshwabkeh, Mohammed Ali Maher; Almajali, Fayez Abdulqader (Journal of Humanities & Social Sciences, 2022)
This study aimed to identify the factors leading to voter buying in the elections of the Eighteenth Jordanian House of Representatives from the voters’ point of view. To achieve this goal, the descriptive survey method was used, the study sample, which was selected by the cluster method, consisted of (836) male and female voters. The study concluded that the most important reasons that push voters to sell their electoral votes are the bad economic conditions, the voters’ conviction of the futility of the electoral process, the unfair competition between some candidates, weak oversight over the electoral process, lack of confidence among voters in the feasibility of choosing a competent candidate, the absence of deterrent legislation to control the sale and purchase of votes, which have negative effects represented in perpetuating the weakness of parliaments, through the production of ineffective parliaments that are unable to perform my mission oversight and legislation, in addition to negatively affecting development and political reform, by rooting corruption in Jordanian society, and depriving the voter of their right to participate and express their opinion on the performance of the Parliament. In light of the results reached, the study recommended a review of the legislation criminalizing the phenomenon of buying electoral votes, and toughening the penalty for these actions because of their negative and destructive repercussions on the process of development, political reform and democracy, and raising awareness of the dangers of buying and selling electoral votes by all institutions of political socialization institutions, especially educational and religious institutions, civil society institutions and the media.